2020
DOI: 10.3390/app10031037
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Myeloperoxidase Levels on Periodontal Disease: An Applied Clinical Study

Abstract: In this trial, we evaluated the influence on plasma and salivary myeloperoxidase (MPO) levels of periodontal health, coronary heart disease (CHD), periodontitis, or both periodontitis and CHD. Clinical and periodontal parameters were collected from periodontitis patients (n = 31), CHD patients (n = 31), patients with both periodontitis and CHD (n = 31), and from healthy patients (n = 31) together with saliva and plasma samples. The median concentrations of salivary and plasma MPO were statistically higher in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 66 publications
0
4
0
Order By: Relevance
“…Therefore, saliva thus appears as an excellent candidate matrix for evaluating the general redox status (balance between oxidants and antioxidants) of an individual. It is important to note, however, that results may be affected by dental hygiene or local oral infection [94]. In our study, the majority of individual PAOT-Saliva Scores were low as compared to the reference interval (Figure S3).…”
Section: (C) Paot ® -Scores and Correlations With Os Plasma Biomarkersmentioning
confidence: 58%
“…Therefore, saliva thus appears as an excellent candidate matrix for evaluating the general redox status (balance between oxidants and antioxidants) of an individual. It is important to note, however, that results may be affected by dental hygiene or local oral infection [94]. In our study, the majority of individual PAOT-Saliva Scores were low as compared to the reference interval (Figure S3).…”
Section: (C) Paot ® -Scores and Correlations With Os Plasma Biomarkersmentioning
confidence: 58%
“…The authors found that there was no statistically significant association between facial typology and gingival biotype. Polizzi et al, in their report, have underlined the fundamental role of Myeloperoxidase in the alveolar bone loss during periodontitis [13], while Byun et al have shown the role exerted of periodontitis in patients that undergo tonsillectomy [14].…”
Section: Periodontal Diseasementioning
confidence: 99%
“…The study by Polizzi et al [35] presented that patients with coronary heart disease demonstrated significantly elevated salivary and plasma levels of MPO, regardless of periodontal status. Based on the multivariate regression analysis, in these patients, salivary MPO concentrations could be predicted by CRP and total cholesterol levels.…”
Section: Cardiovascular Diseasesmentioning
confidence: 99%